Pengaruh Fasilitas, Inovasi, dan Kualitas Pelayanan Terhadap Minat Pengguna Bus Batik Solo Trans : Studi pada Pengguna Bus Trans Solo di Koridor 4 - Destia Madiya Ratri; Asnawi Hidayat; Titin Hargyatni; Pemilia Sulistyowati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the growing public demand for reliable and high-quality public transportation services such as the Trans Solo Bus on corridor 4. The purpose of this research is to analyze the influence of Facilities, Innovation, and Service Quality on User Interest, both partially and simultaneously. This study employs a quantitative method with a sample of 100 respondents who are users of the Trans Solo Bus on corridor 4. Data were collected through questionnaires and analyzed using IBM SPSS Statistics through several tests, including validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results revealed that Facilities, Innovation, and Service Quality significantly influence User Interest, either individually or simultaneously. These findings imply that improving facilities, implementing continuous innovation, and ensuring high service quality can increase public interest in using Trans Solo Bus services, thus supporting the development of sustainable urban transportation.